Электромеханические аналогии - Дьяков, В. А. (ХНУРЭ, 2012)
Method of electromechanical analogies (EMA) used for system, which consist elements with considered and dedicated useless and combined systems, combine other elements into. Electromechanical analogies have practice using in modeling microelectromechanical systems (MEMS).
Keywords: MEMS; EMA; микроэлектромеханические системы; метод электромеханических аналогий